2005
DOI: 10.1248/bpb.28.253
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Flavonoids toward Cultured Normal Human Cells

Abstract: Flavonoids are a group of plant polyphenols and are ubiquitously found in plants. 1,2) Fruits and vegetables, as well as popular beverages such as wine, tea, and coffee, are the main dietary sources of flavonoids. It has been reported that flavonoids show pharmacological effects such as antioxidant, 3,4) antiviral, 5) antitumor, 6) and antiinflammatory activities. 7) In particular, their antioxidant activity has attracted much attention as a possible dietary preventive against cardiovascular and neurodegenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
145
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(173 citation statements)
references
References 37 publications
17
145
1
2
Order By: Relevance
“…Under our conditions, rutin did not show quercetin-like toxic effect in PC12 cells, as previously reported in human promyeloleukemic HL-60 cells 27) and endothelial cells. 10) Some reports showed that rutin could not show quercetin-like effect on undifferentiated and differentiated PC12 cells. 28,29) However, both rutin and quercetin showed similar effect, 20,30) and quercetin-3-o-galactoside showed protective effects against cytotoxicity induced by oxidative stress in PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under our conditions, rutin did not show quercetin-like toxic effect in PC12 cells, as previously reported in human promyeloleukemic HL-60 cells 27) and endothelial cells. 10) Some reports showed that rutin could not show quercetin-like effect on undifferentiated and differentiated PC12 cells. 28,29) However, both rutin and quercetin showed similar effect, 20,30) and quercetin-3-o-galactoside showed protective effects against cytotoxicity induced by oxidative stress in PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…7,8) Flavonoids including quercetin caused apoptosis in carcinoma/cancer cells 2,9) and showed cytotoxicity in normal cells including human umbilical vein endothelial cells. 10) The neuronal density of the hippocampus in gerbils subjected to infusion of quercetin to the ventricle was significantly lower than that in control. 11) Thus, the effects of quercetin on cell death and/or apoptosis in cells including neuronal cells have not been well confirmed.…”
mentioning
confidence: 89%
“…After the treatment, the cells were washed and treated either with a 10 % MTT solution or with a 1 % neutral red solution to determine cell survival (13,14). The absorbance of formazan (540 nm) or neutral red (492 nm) imported into cellular lysosome was measured using a microtitre reader (Cecil Instruments Ltd., Technical Centre Cambridge, UK) and compared with the absorbance measured in untreated (control) cells.…”
Section: Cell Survivalmentioning
confidence: 99%
“…Cell survival was calculated relative to control. The experiments were repeated three times (13,14).…”
Section: Cell Survivalmentioning
confidence: 99%
“…In the latter case, 0.02x corresponds to a concentration 50 times lower than the original extract concentration. After 48 and 72 hours (period of early and late exponential phase), DMEM was removed, and cells incubated with a 10 % MTT solution (15,16). Viable cells have active mitochondrial dehydrogenase enzymes which metabolise yellow-coloured tetrazolium salt into a blue formazan.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%